A SYSTEMATIC REVIEW OF MANUAL AND EQUIPMENT-BASED DEMOLITION TECHNIQUES FOR LOW-RISE BUILDINGS: TECHNICAL PERFORMANCE, SAFETY IMPLICATIONS, AND METHOD SELECTION CRITERIA - Raja Agung Hasudungan Simanjuntak; Mardis Darwis; Risha Utami; Bahdin Ahad Badia; Fachrizal Cesar Putra (universitas teuku umar, 2026)
Low-rise buildings, broadly defined as structures of one to four storeys, represent the dominant residential and small commercial building typology in many countries, particularly across Southeast Asia, Sub-Saharan Africa, Latin America, and parts of the Middle East. Their demolition—whether for urban regeneration, post-disaster clearance, or individual redevelopment—spans a wide spectrum of approaches, from entirely manual hand-tool operations to fully mechanised excavator-based processes. This systematic review comprehensively examines the principal manual and equipment-based demolition techniques applicable to low-rise buildings, analysing each in terms of technical characteristics, operational requirements, safety implications, material recovery potential, and economic performance. The factors governing method selection—including structural typology, site access constraints, proximity to adjacent structures, project budget, and the presence of hazardous materials—are also critically examined. Two structured summary tables are presented: a comparative performance overview and a multi-criteria decision matrix to guide method selection in practice. The review concludes that no single demolition technique is universally optimal; the most appropriate approach is determined by a combination of site-specific, technical, economic, and regulatory factors. Key knowledge gaps are identified, with particular emphasis on developing-country contexts where low-rise demolition is most prevalent yet least formally regulated. Low-rise buildings, broadly defined as structures of one to four storeys, represent the dominant residential and small commercial building typology in many countries, particularly across Southeast Asia, Sub-Saharan Africa, Latin America, and parts of the Middle East. Their demolition—whether for urban regeneration, post-disaster clearance, or individual redevelopment—spans a wide spectrum of approaches, from entirely manual hand-tool operations to fully mechanised excavator-based processes. This systematic review comprehensively examines the principal manual and equipment-based demolition techniques applicable to low-rise buildings, analysing each in terms of technical characteristics, operational requirements, safety implications, material recovery potential, and economic performance. The factors governing method selection—including structural typology, site access constraints, proximity to adjacent structures, project budget, and the presence of hazardous materials—are also critically examined. Two structured summary tables are presented: a comparative performance overview and a multi-criteria decision matrix to guide method selection in practice. The review concludes that no single demolition technique is universally optimal; the most appropriate approach is determined by a combination of site-specific, technical, economic, and regulatory factors. Key knowledge gaps are identified, with particular emphasis on developing-country contexts where low-rise demolition is most prevalent yet least formally regulated.